Israel in the wilderness : interpretations of the biblical narratives in Jewish and Christian traditions - Pomykala, Kenneth (Themes in biblical narrative, 2008)
Examines how stories from the biblical narrative of Israel in the Wilderness (Exodus 16-Deuteronomy 34) were interpreted by later Jewish and Christian writers (ca 400 BCE-500 CE).